Cancer Treatment: Integrating Artificial Intelligence and Nanotechnology for Precision Cancer Medicine (Adv. Mater. 13/2020). Issue 13 (1st April 2020) - Adir, Omer; Poley, Maria; Chen, Gal; Froim, Sahar; Krinsky, Nitzan; Shklover, Jeny; Shainsky‐Roitman, Janna; Lammers, Twan; Schroeder, Avi
Abstract : Artificial intelligence (AI) and nanotechnology are instrumental in realizing the goal of precision medicine—tailoring the best treatment for each cancer patient. Recent conversion between these fields is enabling better patient data acquisition and improved design of nanomaterials. Fundamental concepts in AI and the contributions of nanotechnology and AI to the future of precision cancer medicine are reviewed by Avi Schroeder and co‐workers in article number 1901989 . Cover art ‐ Maayan Harel.